2020
DOI: 10.1039/c9cc08182h
|View full text |Cite
|
Sign up to set email alerts
|

Combination of gem-dinitromethyl functionality and a 5-amino-1,3,4-oxadiazole framework for zwitterionic energetic materials

Abstract: A series of zwitterionic energetic materials was reported, which exhibited higher densities and better detonation performances than common energetic salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…In contrast to 1,2,4-oxadiazole and 1,2,5-oxadiazole, which constitute several energetic materials through a single ring in combination with various explosophoric groups (e. g., amino, nitro, nitramine, and dinitromethyl functionalities), there are a limited number of energetic materials originating from monocyclic 1,3,4-oxadiazole. Zhang et al [49] synthesized two zwitterionic energetic compounds (4 and 6) consisting of a gem-dinitromethyl functional group and an 5-amino-1,3,4-oxadiazole skeleton. Among them, the zwitterionic compound (5-iminio-4,5-dihydro-1,3,4-oxadiazol-2yl)dinitromethanide (4) was synthesized using a four-step synthetic method using commercially available ethyl potassium malonate as the starting material (Scheme 3).…”
Section: Energetic Monocyclic 134-oxadiazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to 1,2,4-oxadiazole and 1,2,5-oxadiazole, which constitute several energetic materials through a single ring in combination with various explosophoric groups (e. g., amino, nitro, nitramine, and dinitromethyl functionalities), there are a limited number of energetic materials originating from monocyclic 1,3,4-oxadiazole. Zhang et al [49] synthesized two zwitterionic energetic compounds (4 and 6) consisting of a gem-dinitromethyl functional group and an 5-amino-1,3,4-oxadiazole skeleton. Among them, the zwitterionic compound (5-iminio-4,5-dihydro-1,3,4-oxadiazol-2yl)dinitromethanide (4) was synthesized using a four-step synthetic method using commercially available ethyl potassium malonate as the starting material (Scheme 3).…”
Section: Energetic Monocyclic 134-oxadiazolesmentioning
confidence: 99%
“…In the synthesis route shown in Scheme 3, intermediate 3 is mechanically sensitive, while compound 2 exhibits poor stability and is not suitable for long-term storage [49]. Therefore, this method to synthesize zwitterionic compounds and their salts is not suitable owing to the unstable intermediates posing potential risks during the preparation process.…”
Section: Energetic Monocyclic 134-oxadiazolesmentioning
confidence: 99%
“…11 More recently, it has been shown that zwitterionic energetic materials are able to combine high performance through increased density while also increasing stability through the electrostatic interactions within the same molecule. [12][13][14][15][16][17] N-oxides are widely used in energetic materials due to their ability to increase performance and stability of a compound. 18,19 Introduction of N-oxides oen leads to increased stability of heterocyclic backbones while also helping to increase oxygen balance.…”
Section: Introductionmentioning
confidence: 99%
“… 11 More recently, it has been shown that zwitterionic energetic materials are able to combine high performance through increased density while also increasing stability through the electrostatic interactions within the same molecule. 12–17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation